ANALYSIS OF THE IMPACT OF FOREIGN IT BUSINESS ON THE LANDSCAPE OF CYBERSECURITY THREATS TO THE STATE - Khokhlachova, Yulia; Davydiuk, Andrii; Zubok, Vitalii (Ukrainian Information Security Research Journal, 2023)
The development of the IT industry contributes to the scaling of businesses providing digital services. The level of process automation in both public and private organizations is increasing. There is a growing demand for computing resources. Businesses in the data centre sphere are scaling to meet the needs not only of users within one country but also of others. At the same time, users from different countries are not limited in their choice of service providers. They are building their own IT businesses using the resources of data centres in other countries. Such a system of trans bordered relations has been built for many years, and its impact on internal economic and social processes in different countries is also growing. In our time, it is relevant to define the concept of a data network, which can be understood as a set of business connections between citizens of different countries in the field of providing digital services and relationships between data centres. Currently, there is no control over the development of data networks, particularly no approaches to measuring the impact of cyber risks of foreign IT businesses on economic and social processes in a country. These networks are characterized by synergistic development. The war in Ukraine has shown that the presence of Russian IT businesses facilitated a series of cyber-attacks aimed at disrupting the functioning of critical infrastructure, government authorities, and businesses. Therefore, it is undeniable that state security services are involved in deploying their own data networks to influence other countries. This work is dedicated to analyzing the impact of foreign IT businesses on a country’s cybersecurity.